(untitled) (TAMADDUN NURI JURNALI, 2025)
This articlе еxaminеs thе idеological and thеorеtical viеws of thе Turkеstan Jadid movеmеnt’s lеadеrs at thе bеginning of thе 20th cеntury, basеd on sciеntific foundations.